MIXED EDUCATION – AS AN EFFECTIVE MEANS OF DEVELOPING INFORMATION-ANALYTICAL COMPETENCE IN FUTURE HISTORIANS (Scientific journal of the Fergana State University, 2023)
In this article, the origin of blended learning, different opinions and views about the term blended learning are discussed. Blended learning is considered as a new method of distance learning with the help of technology and the Internet in order to improve student learning, change the methods of teaching teachers, blended learning combines different models of traditional and distance learning, and It is argued that it is a learning strategy that uses multiple forms of technology.